Clinical Onset of Celiac Disease after an Episode of Campylobacter jejuni Enteritis - EF Verdu; M Mauro; J Bourgeois; D Armstrong (Canadian Journal of Gastroenterology)
The present report describes a young woman with no previous gastrointestinal complaints who was initially diagnosed with postinfective irritable bowel syndrome (IBS) after a confirmed case of Campylobacter jejuni enteritis. However, because of persistent diarrhea, new-onset bloating and the development of iron and vitamin deficiencies, serological markers for celiac disease (CD) were evaluated. A positive tissue transglutaminase immunoglobulin A antibody test and repeat endoscopy with duodenal biopsy showing a Marsh IIIa lesion confirmed the diagnosis of CD. Infectious gastroenteritis is a well-established risk factor for the development of IBS, and there is recent evidence that it could play a role in the initiation and exacerbation of inflammatory bowel disease. The present case suggests that the clinical expression of CD can be unmasked by an acute gastrointestinal infection and supports the hypothesis that environmental factors other than gliadin may play a role in the clinical onset of CD in a genetically susceptible host. The increasing availability of serological testing and upper endoscopy has led to increasingly frequent diagnoses of CD and recognition that it may mimic IBS. The present case findings suggest that CD should be considered in the differential diagnosis of persistent IBS-like symptoms after an episode of infectious gastroenteritis.